Kinesthetic Audio Media Innovation with Local Wisdom for Reading Literacy of Visual Sensory Disabilities - Irfai Fathurohman; Riyan Dwi Cahyaningsih; Isna Fatkhur Rohmah (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
The difficulty of accessing visual literacy learning for people with visual sensory disabilities is a major challenge that must be addressed. This challenge presents other problems, such as a lack of ability to understand the main idea and important information in a text. Inclusive and innovative learning with appropriate learning strategies is highly necessary for visually impaired individuals. This research develops and tests the effectiveness of audio-kinesthetic-based inclusive learning media with local wisdom content. This is intended as a means of improving reading literacy skills for visually impaired individuals, implemented at the Social Service Home for the Visually Impaired (PPSDSN) Pendowo, Kudus Regency. A descriptive qualitative method with a case study research design was chosen to gain a deeper understanding of the application of audio-kinesthetic media based on local wisdom in a natural context. The research results show an 85% increase in information comprehension and the ability to retell the content of the reading among participants. The integration of local cultural elements into audio-kinesthetic media, namely folk tales, gamelan rhythms, and simple kinaesthetic movements, was able to increase attention, active engagement, and the ability to understand main ideas in visually impaired participants. These results indicate that audio-kinesthetic media loaded with local wisdom can strengthen emotional bonds, social communication, and functional literacy skills in visually impaired individuals.